Atlas of Structural Geology - Mukherjee, Soumyajit (Amsterdam : Elsevier Ltd., 2015)
Atlas of Structural Geology features a broad and inclusive range of high-quality meso- and micro-scale full-color photographs, descriptions, and captions related to the deformation of rocks and geologic structures. It is a multi-contributed, comprehensive reference that includes submissions from many of the world's leading structural geologists, making it the most thorough and comprehensive reference available to the scientific community. All types of structures are featured, including structures related to ductile and brittle shear zones, sigma- and delta-structures, mineral fish, duplexe.
Front Cover; Atlas of Structural Geology; Copyright; Contents; List of Contributors; Preface; Acknowledgments; Chapter 1 -- Folds; REFERENCES; Chapter 2 -- Ductile Shear Zones; REFERENCES; Chapter 3 -- Brittle Faults; REFERENCES; Chapter 4 -- Boudins and Mullions; REFERENCES; Chapter 5 -- Veins; REFERENCES; Chapter 6 -- Various Structures; REFERENCES; Author Index; Subject Index.
Includes bibliographical references and indexes.
Vendor-supplied metadata.
Keywords: Geology, Structural -- Atlases; SCIENCE -- Earth Sciences -- Geography; SCIENCE -- Earth Sciences -- Geology; Geology, Structural; Strukturell geologi; Electronic books; Scientific atlases; Electronic book